The Effect Of Work Environment and Discipline of Work on Performance Of Employees - Veramika Sembiring (JURNAL GLOBAL MANAJEMEN, 2021)
This study aims to determine the partial and simultaneous effect of work discipline and work environment on the performance of Dinas Pendidikan Kabupaten Karo. This research is a quantitative research, where the research instrument is a questionnaire. The population and sample in this study were all employees of the Dinas Pendidikan Kabupaten Karo as many as 42 people. Instrument testing in this study was conducted using validity and reliability tests. The data analysis technique in this study uses multiple linear regression analysis techniques. The results showed that the work environment has a positive and significant effect on employee performance, where the t value (2.452) is greater than the t table value (2.015), and the significance value is 0.019 less than 0.05. Work discipline has a positive and significant effect on employee performance, where the t value (6.670) is greater than the t table value (2.015), and the significance value is 0.000 less than 0.05. Work environment and work discipline together have a positive and significant effect on employee performance, where the calculated F value (33.789) is greater than the F table value (2.83), and the significance value is 0.000 less than 0.05. The amount of influence of the independent variables (work environment and work discipline) on the dependent variable (employee performance) is 63.4%, while the remaining 36.6% is influenced by other factors not examined in this study.